设\( {e^{ - x}} \) 是\( f(x) \) 的一个原函数,则\( \int {xf(x)dx = } \) ( )
A: \( {e^{ - x}}(1 - x) + C \)
B: \( {e^{ - x}}(x + 1) + C \)
C: \( {e^{ - x}}(x - 1) + C \)
D: \( - {e^{ - x}}(x + 1) + C \)
A: \( {e^{ - x}}(1 - x) + C \)
B: \( {e^{ - x}}(x + 1) + C \)
C: \( {e^{ - x}}(x - 1) + C \)
D: \( - {e^{ - x}}(x + 1) + C \)
举一反三
- 若\( \int {f(x)dx = F(x) + C} \),则\( \int { { e^{ - x}}f({e^{ - x}})dx = } \)( ) A: \(- F({e^{-x}}) + C \) B: \( F({e^x}) + C \) C: \( F({e^{-x}}) + C \) D: \(- F({e^x}) + C \)
- 若F(x)为f(x)的一个原函数,则∫xf’(x)dx=______。 A: xF’(x)-f(x)+C B: xF’(x)-F(x)+C C: xf’(x)-F(x)+C D: xf’(x)-f(x)+C
- 设$F(x)=\int_0^x e^{x-t}dt$, 则$F'(x)=$ A: $0$ B: $1$ C: $-e^x$ D: $e^x$
- 若\( \int {f(x)dx = {x^2} + C} \),则\( \int {xf(1 - {x^2})dx = } \)( ) A: \( 2{(1 - {x^2})^2} + C \) B: \( - {1 \over 2}{(1 - {x^2})^2} + C \) C: \( {1 \over 2}{(1 - {x^2})^2} + C \) D: \( - 2{(1 - {x^2})^2} + C \)
- 设随机变量X服从参数为2的泊松分布,则以下结果正确的是 A: E(X)=D(X) B: P(X=2)=P(X=1) C: P(X=0)=P(X=1) D: P(X≤1)=P(X=2) E: P(X≥2︱X≥1)=P(X≥1) F: P(X≥1)+P (X≤1)=1 G: E(X)<D(X) H: E(X)>D(X)